PENGARUH DEBT TO EQUITY RATIO, UKURAN PERUSAHAAN, EARNING PER SHARE, DAN NET PROFIT MARGIN TERHADAP HARGA SAHAM - Nurlita, Ike Fala; Rolanda, Ivo (Jurnal Bisnis dan Manajemen (JBM), 2025)
One of the main drivers of GDP growth in the agricultural sector last quarter was the plantation subsector. International market demand and supply for plantation products can influence stock prices. The average stock price of companies in the Plantation Subsector during the period 2016-2022 experienced fluctuations. This research aims to determine the effect of Debt to Equity Ratio, Company Size, Earnings per Share, and Net Profit Margin on stock prices in Plantation Subsector Companies listed on the Indonesia Stock Exchange for the period 2016-2022. The data used in this research were obtained from financial reports. The sampling technique used was purposive sampling, resulting in 77 data points from a sample of 11 companies. The analysis technique used in this research is multiple linear regression analysis using SPSS version 25.0. The results of this study indicate that the Debt to Equity Ratio and Earnings per Share have a significant effect on stock prices, while Company Size and Net Profit Margin do not have a significant effect on stock prices.